Mammary Stem Cells in Domestic Animals: The Role of ROS - Mario Baratta; Silvia Miretti; Elisabetta Macchi; Paolo Accornero; Eugenio Martignani (Antioxidants, 2018)
Reactive oxygen species (ROS) are produced as a natural byproduct of the normal metabolism of oxygen and play significant roles in cell signaling and homeostasis. Although ROS have been involved in pathological processes as diverse as cancer, cardiovascular disease, and aging, they may to exert an effect even in a physiological context. In the central nervous system, stem cells and hematopoietic stem cells are early progenitors that contain lower levels of ROS than their more mature progeny. These different concentrations have been reported to be crucial for maintaining stem cell function. Mammary gland remodeling has been proposed to be organized through the activation and regulation of cells with stemness, either considered real stem cells or primitive precursors. Given the state of oxidative stress in the mammary gland tissue induced by high milk production, in particular in highly productive dairy cows; several studies have focused on the relationship between adult mammary stem cells and the oxidative state of the gland. The oxidative state of the mammary gland appears to be involved in the initial development and metastasis of breast cancer through interference with mammary cancerous stem cells. This review summarizes some links between the mammary stem and oxidative state of the gland.